SUN-510 Pseudohypoparathyroidism Type 1b Presenting With Fahr Syndrome In An Adolescent. - Chen, Jarreau (J Endocr Soc, 2019)
Background: Fahr syndrome is a condition characterized by the presence of abnormal calcifications in the basal ganglia and cerebral cortex, and has been linked with parathyroid disorders. We report a case of pseudohypoparathyroidism (PHP) type 1b in an adolescent presenting with recurrent seizures and intracranial calcifications. Clinical Case: A 15-year old boy presented with recurrent seizures that were uncontrolled despite treatment with anti-epileptic medications. He was diagnosed with epilepsy at the age of 9 overseas and had also been started on levothyroxine 25 mcg daily for hypothyroidism. He arrived in the US for further evaluation and management. He was initially seen by pediatric neurology wherein lab work-up showed hypocalcemia with a total calcium of 6.6 mg/dL (n 8.5-10.5). CT scan of the brain showed disseminated intracranial cortical and basal ganglia calcifications, consistent with Fahr syndrome. EEG showed generalized background slowing compatible with mild diffuse cerebral dysfunction. He was referred to pediatric endocrinology. At his endocrine visit, growth parameters were normal with height at 81(st) percentile, weight at 88(th) percentile, and BMI at 84(th) percentile. Family history was negative of seizures, thyroid or calcium disorders. He does not have intellectual disability. Physical exam did not reveal any features of Albright hereditary osteodystrophy. Additional lab testing showed ionized calcium 0.79 mmol/L (n 1.1-1.35), phosphorus 8.7 mg/dL (n 2.9-5.1), PTH 439 pg/mL (n 10.0-65.0), alkaline phosphatase (ALP) 308 U/L (n 60-270) and 25-hydroxy vitamin D 25.8 ng/mL (n 30-83). Renal function was normal. Findings were suggestive of PTH resistance. Thyroid function showed TSH 4.74 uU/mL (n 0.4-4.6), free T4 1.15 ng/dL (n 0.8-1.7) and negative thyroid antibodies (TPO, TG), suggestive of partial TSH resistance. He was treated with calcium carbonate, calcitriol and ergocalciferol. Levothyroxine was continued. Genetic testing was done which showed a partial loss of methylation in the GNAS exon 1A locus (patient 28%, [normal methylation ≥44%, complete loss of methylation ≤ 12%]), confirming the diagnosis of PHP type 1b. Calcium, phosphorus and ALP levels subsequently normalized with calcium and vitamin D supplementation. PTH improved though remains to be elevated (PTH 67.9 pg/mL). Anti-epileptic medications were weaned off after being seizure-free for more than 2 years. Conclusion: In this case, our patient presented with a distinct triad of epileptic seizure, extensive brain calciﬁcation, and hypocalcemia. This clinical scenario should prompt diagnostic evaluation for PHP as a treatable cause of epileptic seizures in children. Genetic testing for PHP type 1b showed partial loss of methylation in the GNAS locus, which was sufficient to cause disease.